Gender democracy in Colombian regulations, a long road for equality (2018)
The gender approach is an issue that has been under discussion and development worldwide for more than 30 years. Therefore, it has been protected by international treaties and instruments, analyzed by the doctrine and legally regulated in laws, decrees and resolutions and other legal sources. This issue has been addressed by Colombian legislation, which is why this article aims to analyze democracy and gender equity in the national context. The methodological proposal is based on a qualitative method and a documentary technique. It is concluded that the gender perspective in Colombian democracy, although it has made progress in its regulations, has a long way to go to achieve its real effectiveness, as stated in the 1991 Constitution.